Peran Kader Terhadap Peningkatan Gizi Balita Di Desa Banyuraden Sleman Yogyakarta - Hardiyanti, Putri; , Endang Zulaicha Susilaningsih, S.Kp., M.Kep (2017)
Background: The development of health in the period of 2015-2019 is Program Indonesia Sehat (Program of Healthy Indonesia) with a target to increase the society's levels of health and nutrient status through the efforts of health and community empowerment by forming cadres. Cadre is a central point in implementing activities, participation and activeness in Posyandu (Integrated Service Post) and is hoped to be able to mobilize the participation of society. The role of cadre is one of the government's efforts in community empowerment to decrease the level of mortality of infants and children under five and to increase the health level of society. The Purposes of Research: This research aims to know the correlation between the role of cadre and the nutrient increase of the children under five in Banyuraden village, Sleman, Yogyakarta. Method of Research: Kind of this research is quantitative by using a cross-sectional approach. Samples of the research are as many as 85 respondents by using the technique of sampling of proportional stratified random sampling. Instrument of this research used questionnaire. The results of the research: The role of cadre is as many as 63 (74.1%) respondents, meanwhile the nutrient increase of the children under five is 62 (72.9%) respondents. The results of the analysis through the Spearman-rank test obtained the p value = 0,000, the value of rho = 0,850 that meant that there is a correlation between the role of cadre and the nutrient increase of children under five. Conclusion: There is a significant correlation between the role of cadre and the the nutrient increase of children under five in Banyuraden village, Sleman, Yogyakarta.